1972
DOI: 10.1111/j.1399-0039.1972.tb00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sclerosis: Association with HL—A3

Abstract: The incidence of HL—A3 among 94 patients with a diagnosis of multiple sclerosis (MS) was significantly higher than for 871 normal persons. In addition, some increase in Te58 and decrease in HL—A2 and Te60 frequencies was noted. The well‐known higher incidence of MS among Caucasians than among Orientals is paralleled by the higher incidence of HL—A3 and Te58 among Caucasians and a lower incidence of Te60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
85
0
7

Year Published

1974
1974
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(97 citation statements)
references
References 7 publications
5
85
0
7
Order By: Relevance
“…As described above, the first genetic associations identified in MS were found for HLA class I alleles using serologic typing of HLA antigens on leukocytes Jersild et al, 1972Jersild et al, , 1973Naito et al, 1972). When HLA class II alleles were also associated with MS susceptibility, it was proposed that the class I associations were accounted for by linkage disequilibrium with the class II loci (Winchester et al, 1975;Compston et al, 1976;Terasaki et al, 1976).…”
Section: The Mhc and Ms Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As described above, the first genetic associations identified in MS were found for HLA class I alleles using serologic typing of HLA antigens on leukocytes Jersild et al, 1972Jersild et al, , 1973Naito et al, 1972). When HLA class II alleles were also associated with MS susceptibility, it was proposed that the class I associations were accounted for by linkage disequilibrium with the class II loci (Winchester et al, 1975;Compston et al, 1976;Terasaki et al, 1976).…”
Section: The Mhc and Ms Susceptibilitymentioning
confidence: 99%
“…These early studies found that certain cell surface proteins (antigens), that are present on the membranes of peripheral blood mononuclear cells, were overrepresented in MS patients compared to unaffected controls. The first such antigens to be reported were HLA-A3 Naito et al, 1972), followed by HLA-B7 and then HLA-DRw2 (Jersild et al, 1972(Jersild et al, , 1973Winchester et al, 1975;Compston et al, 1976;Terasaki et al, 1976). As it turned out, these HLA associations were not independent of each other but rather reflected a common shared haplotype due to the fact that the chromosomal region coding for these proteins was in Assumes lifetime population prevalence of 0.2% (Ebers et al, 2000;Dyment et al, 2004a).…”
Section: Human Leukocyte Antigensmentioning
confidence: 99%
“…By far the most robust genetic determinant of MS susceptibility is genes within the major histocompatibility locus (MHC) at chromosome 6p21 (Bertrams et al, 1972;Naito et al, 1972;Sawcer et al, 2005;Hafler et al, 2007). Allelic variation at human leukocyte antigen (HLA) alleles is associated with MS risk, with the peak signal mapping to the HLA class II region.…”
Section: Human Leukocyte Antigensmentioning
confidence: 99%
“…HLA genes are highly polymorphic, with over 15,000 alleles identified to date (http://hla.alleles.org/nomenclature/index.html). The first evidence of association between HLA and MS risk dates back to 1972, when the frequencies of surface glycoproteins encoded by the HLA-A3 and HLA-B7 class I alleles were found enriched in MS patients using serological reagents (13,14). In the following years, numerous investigations, regardless of sample size and the resolution, have independently replicated the association of the HLA locus with MS risk across all populations studied, in both primary progressive and relapsingremitting patients.…”
Section: The Human Leukocyte Antigen Locus In Msmentioning
confidence: 87%